IN VITRO FERTILIZATION DECISION-MAKING IN COUPLES WITH INFERTILITY: A LITERATURE REVIEW - Wahyuni, Eko Sari; Setyarini, Anggun (Journal of Maternity Care and Reproductive Health, 2024)
Infertility is a reproductive health problem that affects couples of reproductive age in Indonesia. IVF offers hope for couples who have been waiting for a baby for a long time, but the decision needs to be carefully considered. The purpose of this literature review is to examine the factors that influence infertile couples' decision to choosen IVF. The method used in this study is literature review using databases from ProQuest, PubMed, Science Direct, and Google Scholar. The keywords used were "in vitro fertilisation", "decision making of IVF", "factors that influence the decision making of ivf". Articles were systematically screened based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Results: articles published in the database between 2019 until 2024 obtained 10 articles used in this study. Conclusion: from this literature review, it was found that the decision to follow IVF needs to consider various factors and is personal, needs open discussion with the partner, medical team, and closest people. Suggestion: This study is expected to help health workers in managing infertility and providing information to infertile couples. Further research needs to be done on the interaction between factors that encourage couples to follow IVF and develop effective interventions to help infertile couples make decisions and undergo the IVF successfully.